1982
DOI: 10.1007/bf00917308
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro effects of dexamethasone on leukocyte migration in the rat adjuvant arthritis model

Abstract: When polymorphonuclear leukocytes (PMNs) and mononuclear cells were isolated from the blood of dexamethasone-treated normal rats, in vitro mononuclear cell migration was inhibited and PMN migration was stimulated in comparison to controls. Inflammogen-induced PMNs showed inhibited cell migration due to dexamethasone treatment. Gamma camera imaging was then used to detect cells in vivo after labeling with indium-111. When the dexamethasone-treated blood cells were injected into adjuvant arthritis diseased rats,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Cortisone acetate, for example, augments PMN accumulation in the livers of Listeria-infected mice (34). Dexamethasone enhances PMN migration in vitro but has the opposite effect on macrophages (46).…”
Section: Days After Intraperitoneal Infectionmentioning
confidence: 99%
“…Cortisone acetate, for example, augments PMN accumulation in the livers of Listeria-infected mice (34). Dexamethasone enhances PMN migration in vitro but has the opposite effect on macrophages (46).…”
Section: Days After Intraperitoneal Infectionmentioning
confidence: 99%
“…51 The overall increased proteolytic activity caused during the inflammatory response may affect the dialysis probes by degrading or destroying different probe components, especially the tubing connections that are glued. The reduction in the inflam- Other studies have demonstrated that the monocyte infiltration at the implant site is reduced by releasing dexamethasone, 52,53 but no evidence was provided regarding the variation of capsule thickness or the formation of collagen or blood capillaries. With the exception of day 7 and 10 VB 12 EE%, the calibration of implanted microdialysis probes was not altered as compared to controls when locally infusing dex-phos.…”
Section: Discussionmentioning
confidence: 99%